Pengaruh dukungan sosial keluarga terhadap harga diri perempuan korban kekerasan dalam pacaran - Inggit Amithasari; Husnul Khotimah (University of Merdeka Malang, 2021)
Violence in dating (KDP) is violence both physically, psychologically, sexually and economically that occurs in an unmarried couple. It is not uncommon for women who are victims of dating violence to feel that they have low self-esteem. The purpose of this study was to determine the effect of family social support on self-esteem. This research is quantitative non experimental. The sample in this study was 100 women victims of dating violence. Using accidental sampling technique, with measuring tools for family social support scale (28 valid) and self-esteem scale (26 valid) in the form of a Likert scale. The reliability coefficient is 0.861 for the family social support variable and 0.850 for the self-esteem variable. The results of the hypothesis using the T test for family social support variables are 0.004. a significant value of 0.000 0.05, it is concluded that there is an influence between family social support on self-esteem.